Potensi Kombinasi Ekstrak Daun Kelor (Moringa oliefera) dan Artemisia (Artemisia annua) Sebagai Antimalaria Plasmodium falciparum - Elvina Veronica; Irene Amelia; Kezia Angelina Yunatan; Ni Kadek Sinta Dwi Chrismayanti; Agung Nova Mahendra (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Malaria management like chloroquine and Artemisinin Combination Therapy can have side effects and already resistant so other alternative treatments are needed. This study method uses a literature review from a number of valid and relevant literature. Artemisinin in Artemisia annua plant inhibits PfATPase6, thus making plasmodium Ca homeostasis undisturbed and inhibiting plasmodium growth. Cysteine protease enzymes, ALLN inhibitors, Plasmepsin-2, and Plasmepsin-1 destroy plasmodium in trophozoite and schizont phases by degrading plasmodium protein. Flavonoids in Moringa oliefera leaves increase hemoglobin production and optimize the performance of artemisinin. Kaempferol and other antioxidants in moringa leaves inhibit plasmodium growth through new permeation pathways by inhibiting membrane ordering during the intraerythrocytic phase and inhibiting the degradation process of hemoglobin so that plasmodium can’t develop well. The amount of Moringa leaves can fulfill daily nutritional needs and overcome malnutrition. The combination of artemisia and moringa leaves can be used as an alternative to malaria medicine that is caused by plasmodium falciparum infection because the combination of the two substances is proven to be more effective in inhibiting Plasmodium berghei in experimental animals, enhancing the immune system, and meeting nutritional needs compared to the use of artemisinin and moringa leaves alone. Need further investigation about this thing.